Wage Inequality in Post-Reform Mexico - Airola, Jim; Juhn, Chinhui (Journal of Income Distribution®, 2008)
Using the ENIGH covering 1984-2002, we analyze wages and employmentin Mexico after trade liberalization and domestic reforms.We find that wage inequality and returns to post-secondary schoolingincreased rapidly during 1984-1994 but stabilized since that period.The end of inequality growth was due to a severe macroeconomic crisiswhich adversely impacted the better educated, an increase in educationlevels at the end of the 1990s, and a slowdown in skill demand in thelatter half of the 1990s. Between industry shifts, consistent with tradebasedexplanations, account for a part of the increase in skill demandduring 1984-1994, but these types of movements actually reduced thedemand for skill in the latter part of the 1990s. The equalizing impactof trade was offset by within-industry demand shifts which continuedto favor more educated workers. The Mexican experience in the 1990ssuggests that market-oriented reforms have a sharp initial impact oninequality which dissipates over time but further that opening the economyto trade, foreign capital, and global markets does lead to a morelong-run increase in the demand for skill.